Tumor perfusion assessed by dynamic contrast-enhanced MRI correlates to the grading of renal cell carcinoma: Initial results - Palmowski, Moritz; Schifferdecker, Isabel; Zwick, Stefan; Macher-Göppinger, Stephan; Laue, Hendrik; Haferkamp, Axel; Kauczor, Hans-Ulrich; Kiessling, Fabian; Hallscheidt, Peter (European journal of radiology, 2010)
In this study, we investigated whether assessment of the tumor perfusion by dynamic contrast-enhanced magnetic resonance imaging (DCE MRI) enables to estimate the morphologic grading of renal cell carcinomas. A total of 21 patients with suspected renal cell cancer were examined using a Gadobutrol-enhanced, dynamic saturation-recovery, turbo-fast, low-angle shot sequence. Tumor perfusion and the tissue-blood ratio within the entire tumor and the most highly vascularized part of the tumor were calculated according to the model of Miles. Immediately after examination, patients underwent surgery, and the results from imaging were compared with the morphological analysis of the histologic grading. Fourteen patients had G2 tumors, and seven patients had G3 tumors. Significantly higher perfusion values (p<0.05) were obtained in G3 tumors than in G2 tumors when the entire tumor area was considered (1.59±0.44(ml/g/min) vs. 1.08±0.38(ml/g/min)) or its most highly vascularized part (2.14±0.89(ml/g/min) vs. 1.40±0.49(ml/g/min)). By contrast, the tissue-blood ratios did not differ significantly between the two groups. In conclusion, unlike tissue-blood ratio, surrogate parameters of the tumor perfusion determined by DCE MRI seem to allow an estimation of the grading of renal cell carcinoma. However, further studies with high case numbers and including patients with G1 tumors are required to evaluate the full potential and clinical impact.
Online verfügbar 21 June 2009
Gesehen am 23.06.2023